Habituation Training Improves Locomotor Performance in a Forced Running Wheel System in Rats - Toval, Angel; Baños, Raúl; De la Cruz, Ernesto; Morales-Delgado, Nicanor; Pallarés, Jesús G.; Ayad, Abdelmalik; Tseng, Kuei Y.; Ferran, Jose L. (Frontiers in Behavioral Neuroscience, 2017)
Increasing evidence supports that physical activity promotes mental health; and regular exercise may confer positive effects in neurological disorders. There is growing number of reports that requires the analysis of the impact of physical activity in animal models. Exercise in rodents can be performed under voluntary or forced conditions. The former presents the disadvantage that the volume and intensity of exercise varies from subject to subject. On the other hand, a major challenge of the forced training protocol is the low level of performance typically achieved within a given session. Thus, the aim of the present study was to evaluate the effectiveness of gradual increasing of the volumen and intensity (training habituation protocol) to improve the locomotor performance in a forced running-wheel system in rats. Sprague Dawley rats were randomly assigned to either a group that received an exercise training habituation protocol, or a control group. The locomotor performance during forced running was assessed by an incremental exercise test. The experimental results reveals that the total running time and the distance covered by habituated rats was significantly higher than in control ones. We conclude that the exercise habituation protocol improves the locomotor performance in forced running wheels.